Revisiting Authorisation Liability in Copyright Law - SAW, Cheng Lim (Institutional Knowledge at Singapore Management University, 2012)
In this article, the authors revisit the origins and purpose of the law on authorising infringement and propose that the word “authorise” should bear the dictionary meaning of “sanction, approve, countenance”, in lieu of the phrase “grant or purported grant” as adopted in the CBS Songs Ltd v Amstrad Consumer Electronics plc ([1988] AC 1013) decision. The authors will also examine a non-exhaustive list of factors for determining authorisation liability. The suggested approach seeks to expand the scope of indirect copyright liability in Singapore, which is necessary in the face of increasing incursions into the sphere of copyright protection.